Caught between is and ought: The Moral Dissonance Model - Te Brake, Hans; Nauta, Bart (Frontiers in Psychiatry, 2022)
Considerable academic effort has been invested in explaining the causes of, and processes behind moral injury. These efforts are mostly focused on assessment and treatment within a clinical setting. Collective and social factors contributing to moral injury are often overlooked in current literature. This perspective article considers the role of contextual factors associated with moral injury and proposes a framework that describes their relation to individual aspects. The resulting Moral Dissonance Model (MDM) draws on existing theories and frameworks. The MDM explains how dissonance can occur when the actual behavior–the response to a morally challenging situation–contradicts with morally desirable behavior. Individual and collective factors, which change over time, contribute to the experience of dissonance. The inability to sufficiently solve dissonance can lead to moral injury, but not as a matter of course. The MDM can help to understand the underlying processes of moral distress. It raises awareness of the influence of public debate and controversy, and the resulting changing societal attitudes over time. Its implications and future use are discussed.